Mechanical, thermal and electrical properties of nanostructured CNTs/SiC composites. Issue 2 (1st February 2019) - Lanfant, B.; Leconte, Y.; Debski, N.; Bonnefont, G.; Pinault, M.; Mayne-L′Hermite, M.; Habert, A.; Jorand, Y.; Garnier, V.; Fantozzi, G.; Le Gallet, S.; Bernard, F.
Abstract: Dense SiC-based nanostructured composites reinforced by well-distributed carbon nanotubes (CNTs) were elaborated for the first time by spark plasma sintering (SPS) without sintering additive. Microstructures of materials containing different amounts of CNTs – up to 8.0 vol% – were correlated with their mechanical, electrical and thermal properties. A continuous decrease of the SiC grain size was observed when the amount of CNT was increased, while the evolution of density showed a different behavior that could be explained by the particular combination of SPS technique with the electrical resistivity evolution of the green bodies. Optimal effect of CNTs addition on hardness and toughness was obtained for 3.2 vol% CNTs, with values of 2560 Hv and 4.0 MPa m 1/2, respectively. The decrease in electrical resistivity observed after sintering was ascribed to a combined effect of CNTs with the emergence of structured carbon during the sintering. Enhancement of thermal conductivity with CNTs addition was on the contrary not observed.